PERAN MEDIASI PERCEIVED USEFULNESS DALAM PLATFORM C2C E-COMMERCE - Lily Purwianti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The purpose of this research is to find out the factors that influence in C2C e-commerce. The sample of this study was people who had done online shopping This studyuses PLS in testing hypothesesusing 342 respondents. The results of this study indicate that independent, information quality, trust, perceived ease of use variables have influence on perceived usefulness. Another finding is perceived usefulness influencing on consumer participation (purchase intention, recommendation intention).